Measuring Provincial National Defense Capacity: Evidence from Campus-Based Non-Military Defense Implementation in Java, Indonesia. - Wirawan, Rio; Resti, Anggi Angga; Balqis, Haura Asqo (Technium Social Sciences Journal, 2026)
The concept of national defense has expanded beyond military preparedness toward non-military dimensions emphasizing governance capacity, civic engagement, and institutional resilience. However, empirical measurement of national defense at the sub-national level remains limited, particularly in capturing the role of higher education institutions as non-military actors. This study aims to measure the Provincial National Defense Index (NDI) at the provincial level by utilizing campus-based non-military defense implementation as empirical evidence. This study employs a mixed-methods approach, integrating expert-based focus group discussions and quantitative assessments across higher education institutions in Java, Indonesia. The index is constructed using seven institutional dimensions, including curriculum integration, governance policies, campus activities, budget allocation, symbolic artifacts, publication practices, and civic awareness. The results reveal significant variations in provincial defense capacity, where stronger performance is associated with institutionalized governance, while weaker performance reflects limited financial support and documentation systems. This study contributes to social science and governance literature by offering a novel composite index that links non-military national defense with provincial-level institutional capacity and higher education governance.